Mobility for the cause: the Massachusetts State Navy and inter-service mobility in the Revolutionary War - Dure, Leon (Kansas State University, 2022)
Servicemen during the American Revolution chose to participate in the conflict for many different reasons, and they frequently transitioned among the different types of services available to them on sea and land. This thesis, using the Massachusetts State Navy as a focal point, will examine the ways that revolutionary fighters and colonial authorities worked to balance the former’s contributions to the war effort in an environment where various official and quasi-official military organizations – privateering vessels, state navies, militias, the Continental Army and the Continental Navy – vied for recruits. The Massachusetts State Navy, dedicated to protecting Massachusetts’ coastline, securing necessary trade goods in the face of the British blockade, and raiding British shipping, provided one such option for military service, competing with other Patriot military organizations for recruits. Finding – and retaining – enough seamen was challenging for the Massachusetts State Navy because servicemen might choose to end their military service altogether at the end of an enlistment, move to a privateer or land-based military unit during their current term of service, or desert their posts. This thesis will assess the military careers of ten Patriot servicemen to illustrate the mobility between branches of service that these men and their counterparts often experienced. The thesis will examine the choices that various servicemen made when moving in or out of the Massachusetts State Navy, and the struggle Patriot military forces faced in retaining personnel. While some Patriot servicemen stayed in one military branch for their whole military career, many Patriot sailors and soldiers chose to move from one branch of service to another.
Keywords: American history; Military history